Strengthening of Village Communities in Supporting National Economic Recovery - Rosidah Rosidah (Journal of Governance, 2022)
The national economic crisis faced by the central and regional governments faces considerable challenges in maintaining economic stability due to economic uncertainty that has an impact on economic activity. The purpose of this research is to strengthen the economies of rural communities in the long term by realizing the welfare of rural communities continues to increase through improving the economies of rural communities by fostering business actors by managing village potential. This study uses a qualitative approach to describe social phenomena that occur in rural communities as it seeks to strengthen the village economy. The type of research resulting from the selected qualitative method is descriptive research. These findings on strengthening social capital through community participation need support from local values.